Klebsiella virus UPM2146 lyses multiple drugresistant Klebsiella pneumoniae in vitro and in vivo - Assafiri, Omar; Song, Adelene Ai Lian; Tan, Geok Hun; Hanish, Irwan; Mohd Hashim, Amalia; Yusoff, Khatijah (Public Library of Science, 2021)
Klebsiella pneumoniae are opportunistic bacteria found in the gut. In recent years they have been associated with nosocomial infections. The increased incidence of multiple drug-resistant K. pneumoniae makes it necessary to find new alternatives to treat the disease. In this study, phage UPM2146 was isolated from a polluted lake which can lyse its host K. pneumoniae ATCC BAA-2146. Observation from TEM shows that UPM2146 belongs to Caudoviriales (Order) based on morphological appearance. Whole genome analysis of UPM2146 showed that its genome comprises 160,795 bp encoding for 214 putative open reading frames (ORFs). Phylogenetic analysis revealed that the phage belongs to Ackermannviridae (Family) under the Caudoviriales. UPM2146 produces clear plaques with high titers of 1010 PFU/ml. The phage has an adsorption period of 4 min, latent period of 20 min, rise period of 5 min, and releases approximately 20 PFU/ bacteria at Multiplicity of Infection (MOI) of 0.001. UPM2146 has a narrow host-range and can lyse 5 out of 22 K. pneumoniae isolates (22.72%) based on spot test and efficiency of plating (EOP). The zebrafish larvae model was used to test the efficacy of UPM2146 in lysing its host. Based on colony forming unit counts, UPM2146 was able to completely lyse its host at 10 hours onwards. Moreover, we show that the phage is safe to be used in the treatment against K. pneumoniae infections in the zebrafish model.